Dinamika Psikologis Anak Pelaku Kejahatan Seksual - Khoirunita Ulfiyatun Rochmah; Fathul Lubabin Nuqul (Jurnal Psikologi Tabularasa, 2015)
This research aimed to know the psychological dynamics of child sex offenders. This research was social psychology. Method of the research was qualitative method with phenomenological strategy. Participatns were 5 children from LP Anak Kelas II A Blitar. Participants were sexual offenders. Results from this study show that child sex offenders due to factors impulse or peer support, teenage sex drive increases, and with a broken family relationships.